Analisis User Engagement pada Akun Instagram Perpustakaan di Masa Covid-19 - Wijayanti, Ayu Yuli (Universitas Sebelas Maret Library, 2022)
The Covid-19 pandemic has affected all walks of life, including college libraries which have made their services migrate online by utilizing social media. Instagram has become a common platform used by college libraries to interact with users during the Covid-19 pandemic. Tarumanagara University Library Services in the field of Psychology is one of the libraries in the university environment that uses Instagram media to serve its users. This study aims to photograph how users interact on the library's Instagram account. This research can be categorized as quantitative descriptive to get accurate results with statistical data. Content analysis was conducted to determine content categories based on their objectives. The results of this study indicate that during the pandemic it was found that there were 276 post content, most of which were photos. The average likes per post is only 10, while the number of comments from all posts is only 54. The dominant content category is literary exhibition, which is a content category with the aim of informing collections, references and technical service manuals.